Making Education Game to Choose Healthy Snacks for Children - Vania Wahyu Febriani (SISFORMA, 2017)
One of the learning media is games. Games that can be used as a learning tool can be called as education games. Because children like games, games can make positive effect for them. Children can study while playing games.